Local Wisdom Of Padang Pariaman People In Managing Of “Banned Fish” In Nagari Sikucur - Nefilinda Nefilinda; Jamsari Jamsari (Pancaran Pendidikan, 2017)
One of the unique local wisdoms implemented by the local community in Nagari Sikucur, Padang Pariaman West Sumatera is “banned fish”. However, changes and shifts in people's lifestyles affect the pattern and values adopted by the local community, including the local wisdom of the community in that area. In order to describe the local wisdom in that area, a qualitative study was conducted. This study was aimed to answer some research questions figuring social phenomena related to local wisdom in West Sumatera people. The results showed that management of banned fish in Nagari Sikucur has been implemented as informal public policy in order to preserve fish population in their rivers. Such agreement has successfully conserved the ecosystem while another impact also attracted people in seeing such ecotourist system. Management of such local wisdom is applied in well practice, accepted and bind to the whole society member. People are benefited with such local wisdom by having clean water in the river that can be used for their agricultural activities.